CISSP video mentor - Harris, Shon.; Keeber, Don.; Lester, Mike.; Safari eBooks ([S.l. : Pearson Certification, 2009)
"In these videos, the world's #1 CISSP trainer and her hand-picked team of experts walk you through the skills and concepts you'll need to master and pass the most technical of the CISSP common body of knowledge domains. Five hours of expert-led videos designed to build and test your knowledge of principles of cryptography, authentication codes, IPSec, the OSI model and protocols, 802.11 wireless security, and more!"--Resource description page.
System requirements: Adobe Flash Player, version 8 or higher; or QuickTime Player, version 7.2 or higher; or Windows Media Player, version 11 or higher.
Publisher and date of publication from resource description page (viewed Mar. 11, 2010).
Presenters: Don Keeber, Mike Lester.
Keywords: Computer security -- Examinations; Telecommunications engineers -- Certification -- Examinations; Computer networks -- Security measures -- Examinations; Electronic books